Em nome do pai : outremização e descolonização em Amongst Women - romance e minissérie - Godoy, Beatriz Cristina (2013)
Such was the impact caused on the colonized territories by the colonial expansion that even decades after the withdrawal of the colonizer it is still possible to identify the remaining consequences of this process. Some of these consequences are represented in John McGahern's novel Amongst Women (1990), which is the text being analyzed in the present work making use of post-colonial theories. Relying on the concepts of othering and decolonization it considered the way in which the colonized individuals arising from the colonial situation struggle to adapt to a post-colonial society and also the impossibility of completely extirpating the social, political, economic and cultural remains left behind by the colonizer. The theorists whose work supported this analysis are Memmi, Fanon and Spivak. Following, the homonymous miniseries - produced by the BBC Northern Ireland and RTÉ - was analyzed according to the adaptation and television narrative theories; the main texts here are those of theorists Hutcheon, Brady and Thompson. The analysis of the miniseries focus on the reoccurring characteristics pinpointed in the novel and in which ways the transmutation of media generated a refitting of contente.